Tingkat Kecemasan Siswa Kelas VII SMP Negeri 2 Telagasari dalam Pembelajaran Pendidikan Jasmani Menghadapi Pertemuan Tatap Muka di Sekolah Pada Masa Pandemi Covid 19 - Putra Nova; Ruslan Abdul Gani; Rekha Ratri Julianti (Jurnal Ilmiah Wahana Pendidikan, 2021)
The results of this study indicate that the anxiety level of seventh grade students of SMPN 2 Telagasari in learning physical education facing face-to-face meetings at school during the covid-19 pandemic is in the very high category 0.00% (0 students), high category 23.08% ( 15 students), sufficient category is 46.15% (30 students), low category is 27.68% (18 students), very low category is 3.08% (2 students). The conclusion is that the anxiety level of seventh grade students of SMPN 2 Telagasari in learning physical education facing face-to-face meetings at school during the COVID-19 pandemic based on indicators of state, feeling, reaction, worry, and emotion based on the sum of the scores of all, it was found that the level of student anxiety class VII SMPN 2 Telagasari in learning physical education facing face-to-face meetings is in the sufficient category. The results of this study are expected to be able to carry out face-to-face learning in schools by increasing strict health protocols to reduce the spread of COVID-19 and direct practical learning to obtain more optimal results.